Frank Ankersmit and Eelco Runia: the presence and the otherness of the past. - Froeyman, Anton (Rethinking History, 2012)
This paper consists of two parts. In the first part, I give an in-depth comparison and analysis of the theories of Frank Ankersmit and Eelco Runia, in which I highlight their most important resemblances and differences. What both have in common is their notion of the presence of the past as a ‘presence in absence’. They differ, however, with respect to the character of this past and the role representation plays in making it present. Second, I also argue that for both Ankersmit and Runia, the presence of the past is always the present of our past, which excludes the experience of the otherness of the past, and which opens both theories to the criticisms of being self-centered and nationalistic.